Model Of Local Wisdom Based-Community Empowerment To Control HIV/AIDS - irwan skm (Gorontalo State University, 2020)
The Number of people who living with HIV-AIDS in Gorontalo Province 2015 by age group mostly found in productive age 27-35 years old with the number 87 respondent (87%). It is estimated that They infected in previous years in adolescence.The aim of this research is was to develop amodel of risk behavior AIDS disaggregated by gender, the theory of Plan Behavior was used as a framework og the study, Methods of this study was analytic observational study with cross sectional study design. The Sample was 200 students, in the city of Gorontalo, was obtained through purposive random sampling. The result risk behaviors of AIDS in adolescent behavioral variables not influenced by variables intentions, and beliefs. Model risk behaviors of AIDS showed that variable intention and belief significant effect on behavior, Evaluation models Based on Goodness of fit, teen models on the behavior of otherwise fit the criteria RMSEA value of 0.000 Required smaller than 0.08. Sugestion In order to prevent HIV and AIDS in adolescents it is recommended to conduct interventions that focus on the religious sector.